Silver nanoparticles in denture adhesive: An antimicrobial approach against Candida albicans - Peralta, Laura Catalí Ferreira; Almeida, Nara Ligia Martins; Pontes, Fenelon Martinho Lima [UNESP]; Rinaldo, Daniel [UNESP]; Carneiro, Camila Alves; Neppelenbroek, Karin Hermana; Lara, Vanessa Soares; Porto, Vinicius Carvalho (Elsevier, 2023)
Objective: To evaluate the antimicrobial potential of silver nanoparticles (Ag NPs) synthesized using three different routes (ultraviolet light, Turkevich, and green chemistry method using Glycine max extract) associated with COREGA® denture powder adhesive. Methods: Heat-cured acrylic resin specimens were treated with different Ag NPs associated with the adhesive (AD + Ag UV, AD + Ag Turk, and AD + Ag Gm groups). As controls, the specimens were treated with a combination of adhesive and nystatin (AD + Nyst group), only adhesive (AD group), or submerged on the surface of the specimens (PBS group). After the treatments, biofilms of C. albicans developed for 3, 6, and 12 h on the specimen surfaces. The biofilm was quantified using colony-forming units per milliliter, colorimetric assay, and confocal laser scanning microscopy. Results: Regardless of the period, we observed an inhibition of fungal load and a reduction in metabolic activity and biofilm mass in the resin specimens treated with the combinations AD/Ag NPs, compared to AD and PBS. The antimicrobial action of the AD + Turk and AD + Ag Gm groups was similar than that for the AD + Nyst group in all periods and viability tests, except for the biofilm mass (12 h). Conclusions: The COREGA® adhesive with Ag NPs, mainly those synthesized using the Turkevich and Glycine max methods, showed excellent antimicrobial activity against C. albicans biofilms, maintained for up to 12 h. Clinical significance: The association of Ag NPs to the adhesive can add preventive or therapeutic effects against denture stomatitis, to this prosthetic material.
Keywords: Antimicrobial agents; Candida albicans; Denture stomatitis; Nanotechnology; Silver nanoparticles; Tissue adhesives